Analysis of the Impact of Energy Use on CO2 Emissions: Before, During, and Post-Covid-19 - Sarah Delana Wijaya; Fahmy Rinanda Saputri (G-Tech: Jurnal Teknologi Terapan, 2024)
This article discusses the impact of energy use on CO2 emissions, especially the transition from fossil energy to renewable energy. Since the industrial revolution until today, fossil energy has been the main source of energy. The COVID-19 pandemic played a significant role in transformingthe global energy paradigm. Restrictions on social activities during the pandemic resulted in a drastic decrease in the use of fossil energy and increased the use of renewable energy. A critical analysis of energy consumption, availability of energy sources, and the impact of fossil and renewable energy use provides an overview of the energy transition that is taking place. It can be concluded that this article illustrates the significant changes in energy consumption patterns before, during and after COVID-19.